2003
DOI: 10.1002/ijc.11383
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for multiple oral premalignant lesions

Abstract: Oral leukoplakia, oral submucous fibrosis and erythroplakia are 3 major types of oral premalignant lesions. Multiple oral premalignant lesions may possibly develop due to field cancerization, where carcinogenic exposures can cause simultaneous genetic defects to the upper aerodigestive tract epithelium, putting the epithelium at high risk for development of premalignant lesions at different stages of carcinogenesis. There have been no epidemiological studies on risk or protective factors of the disease. A case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
60
1
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(69 citation statements)
references
References 12 publications
1
60
1
4
Order By: Relevance
“…In an oral cancer screening study in India, tobacco chewing was the most important risk factor for multiple oral premalignant lesions but smoking was not associated with the risk of multiple oral premalignant lesions (Thomas et al, 2003). Considering the fact that the present study showed significantly more oral pre cancer lesion among individuals with other medical ailments, amply demonstrates that tobacco and alcohol users in general are at greater risk for many major chronic diseases.…”
Section: Discussionmentioning
confidence: 41%
“…In an oral cancer screening study in India, tobacco chewing was the most important risk factor for multiple oral premalignant lesions but smoking was not associated with the risk of multiple oral premalignant lesions (Thomas et al, 2003). Considering the fact that the present study showed significantly more oral pre cancer lesion among individuals with other medical ailments, amply demonstrates that tobacco and alcohol users in general are at greater risk for many major chronic diseases.…”
Section: Discussionmentioning
confidence: 41%
“…The most important risk factors for develops OSCC are smoking and chronic alcoholism (9 -11). 75% of all OSCC are related to one or both carcinogenic factors (12,13). An increase in the consumption of tobacco and alcohol in young Mexicans has been reported (11, 14 -16).…”
Section: Discussionmentioning
confidence: 99%
“…Studies show that human papillomavirus (HPV)-16 and HPV-18 are also considered to be the viral etiopathology of oral PMD. [14][15][16] Since oral PMD have a high tendency to transform into malignancy, there is a need to identify these disorders early and prevent their transformation to malignancy by various means.…”
Section: Introductionmentioning
confidence: 99%